An "immobilizing and relocating" strategy for a highly reversible metallic zinc anode. Issue 3 (3rd January 2023) - Yao, Rui; Qian, Long; Zhao, Guangyao; Zhu, Haojie; Qin, Tingting; Xiao, Chengxiang; Lin, Hai; Kang, Feiyu; Zhi, Chunyi; Yang, Cheng
Abstract : The anion end of zwitterions can interact with water around the electrode/electrolyte interface and promote the zinc plating/stripping kinetics, while their cation end can be adsorbed on the metallic zinc surface and homogenize zinc plating/stripping. Abstract : Over the last decade, aqueous metallic zinc batteries have aroused broad attention as a complementary alternative to lithium-ion batteries due to their safe and eco-friendly characteristics. However, the parasitic reactions ( i.e., dendrite growth, by-product formation, and hydrogen evolution) during zinc plating/stripping severely impair the electrochemical stability and reversibility of the metallic zinc anode. Herein, we proposed an "immobilizing and relocating" strategy for managing the electrode–electrolyte interface by introducing bifunctional betaine zwitterions into the baseline electrolyte. We found that the cation end of the zwitterions can be adsorbed onto metallic zinc and homogenize zinc plating/stripping by adjusting the electric field distribution. Meanwhile, the anion end of the zwitterions can interact with the water molecules around the electrode/electrolyte interface through hydrogen bonds and promote the zinc plating/stripping kinetics. Based on this "immobilizing and relocating" strategy, the initial coulombic efficiency (CE) of the zinc plating/stripping in Zn‖Cu half-cells exceeds 94.99% at a current density of 1 mA cm −2, and the average CE reaches 99.93%. A Zn‖MnO2 full cell adopting 20 μm thick zinc stably runs for 500 cycles with a capacity retention of 86.4%. This work provides a new insight into realizing highly reversible metallic zinc anode.